Toxicological effects of transition metal-doped titanium dioxide nanoparticles on goldfish (Carassius auratus) and common carp (Cyprinus carpio) - Pirsaheb, Maghdad; Azadi, Nammam Ali; Miglietta, Maria Lucia; Sayadi, Mohammad Hossein; Blahova, Jana; Fathi, Mokhtar; Mansouri, Borhan (Chemosphere, 2019)
The aim of present study was to assess the toxicological effects of transition metal-doped titanium dioxide nanoparticles (TiO2 NPs) on histopathological changes, behavioral patterns, and antioxidant responses of goldfish (Carassius auratus) and common carp (Cyprinus carpio). The synthesized nanoparticles were confirmed by Transmission Electron Microscopy, Field Emission Scanning Electron Microscopy, X-ray diffraction, UV-visible, and Vibration Sample Magnetometer. Fish in four experimental groups exposed to sub-lethal concentrations of pure TiO2 NPs (10 mg L-1), chromium (Cr), iron (Fe), and nickel (Ni) doped TiO2 NPs for seven days. Statistical analysis of oxidative stress responses in gills showed significant differences in superoxide dismutase, total antioxidant capacity, and malondialdehyde parameters between two species and in all parameters than glutathione peroxidase between experimental groups and control group. In intestine, no significant difference was observed among groups, but oxidative responses were markedly different in all parameters among fish species. The histopathological analysis showed hyperplasia, fusion, and aneurism in the gills as well as degeneration, integration of villi, necrosis and erosion of the intestine. Our findings indicated that compare to pure TiO2 NPs, exposure to transition metals-doped TiO2 NPs induced oxidative stress and histopathological changes in both fish species.
Keywords: TiO(2) NPs; karas zlatý; Carps; Histopathological damages; Animals; Transition metal; Goldfish; Titanium; Antioxidant response; Fish; zvířata; kovové nanočástice; Metal Nanoparticles; kapři; titan